Indonesia Dalam Menjawab Konsep Negara Welfare State dan Tatangannya - Venatius Hadiyono (JURNAL HUKUM, POLITIK DAN KEKUASAAN, 2020)
The concept of a welfare state is the idea that the state is responsible for its citizens, that is, by means of the welfare of its people through services, assistance, protection and prevention of social problems. Indonesia applies this system by adopting a minimal welfare state model, namely by providing a very small budget for social spending. So that social services are provided only for civil servants, Indonesia Military members and private employees who are able to pay the premium. Constitutional support is mentioned in the Indonesian Constitution of 1945, namely Articles 23, 27, 28C, 31, 33, and 34. This is then followed by laws. Number 40 of 2004 concerning the National Social Security System. However, the concept of welfare state is implemented in a minimal model. This is exacerbated by the corruption problems. Indonesia should not only focus on the health sector in realizing the concept of the welfare state, but the education sector can also be a priority to provide an idealistic human resources to create a clean Indonesia for the achievement of the dream of a welfare state.